HGG-20. DNA METHYLATION ANALYSIS OF HIGH-GRADE GLIOMA IN PATIENTS WITH MISMATCH REPAIR DEFICIENCIES. Issue 2 (22nd June 2018) - Dodgshun, Andrew; Fukuoka, Kohei; Campbell, Brittany; Edwards, Melissa; Sexton-Oates, Alexandra; Larouche, Valérie; Magimairajan, Vanan; Lindhorst, Scott; Oren, Michal; Mason, Gary; Crooks, Bruce; Constantini, Shlomi; et al.
Abstract: Patients with constitutional mismatch repair deficiency (CMMRD) are prone to developing high-grade glioma (HGG). These tumours acquire DNA polymerase mutations and become ultra-hypermutant harbouring hundreds of mutations per megabase. The impact of these mutations on methylation profile and the ability of the tool to differentiate MMRD tumours from others is unknown. In order to answer these questions, we performed either 450k/850K methylation analysis on a cohort of 52 CMMRD-HGG and compared them to 148 non-CMMRD HGG and normal brain controls. CMMRD HGG harbouring classic mutations in histone 3 or IDH genes had a methylation profile which clustered closely with non-MMRD tumours harbouring these mutations. Tumours without these alterations exhibited a tendency to hypomethylation with some tumours being extremely hypomethylated in comparison to other HGG. Hypomethylation was unrelated to mutational burden and type of DNA polymerase mutation present. Gene set analysis of methylation patterns revealed enrichment of hypomethylation for cellular pathways involved in cellular metabolism, organelle maintenance, mitotic cell cycle and gene expression. This pattern persisted in subgroup analysis of IDH mutant tumours in patients with and without MMRD. Importantly, this pattern was present in MMRD HGG with mutational burdens <10 mutations/MB and shared between primary and recurrent tumours suggesting that hypomethylation is an early event. CMMR-HGG have unique pattern of hypomethylation which can distinguish them from other paediatric HGG. Several plausible explanations include that hypomethylation in specific pathways confer a survival advantage on the cells which acquire it, or that hypermutations in specific CpG affect methylation patterns in these genes.